Diffuse bronchiectasis and airflow obstruction in granulomatosis with polyangiitis - Barba, Thomas; Khouatra, C.; Traclet J, J.; Cordier, J.F.; Cottin, V. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Parenchymal lung nodes and diffuse intra-alveolar hemorrhage are the archetypal pulmonary manifestations of Granulomatosis with Polyangiitis (GPA). The occurrence of diffuse bronchiectasis and airflow obstruction during GPA is unusual. We report here 3 patients with GPA who developed diffuse bronchiectasis during follow-up. The airflow obstruction seemed then to evolve independently from the GPA itself and ultimately led to respiratory insufficiency. Bronchiectases promoted the occurrence of opportunistic infections, especially with atypical mycobacteria.